PATHOMORPHOLOGICAL CHANGES IN RENAL PARENCHYMA, AFTER MODELING OF ACUTE PYELONEPHRITIS IN MICE, DEPENDING ON THE ABILITY OF BACTERIA TO FORM BIOFILMS. - Mitiuriaeva-Kornijko, I. O.; Vodianyk, A. A.; Lihodievskyy, V. V.; Ponyatovskiy, V. A.; Gniloskurenko, A. V.; Grechukha, Y. O.; Druzenko, M. O.; Kornijko, Y. Y. (Ukrainian Journal of Nephrology and Dialysis, 2017)
Urinary tract infection is one of the most common infectious diseases that affects people of any age and sex. The purpose of our study was to determine morphological changes in acute pyelonephritis, depending on the ability of bacteria strains to form biofilms. Materials and methods. The model of acute pyelonephritis was reproduced by ascending urinary infection model of laboratory mice with clinical isolates of E.coli with low biofilm formation ability (group # 1) and high biofilm formation ability (group # 2), the material was taken on day 7 of the experiment, histological sections were analyzed in comparison with control (group # 3). Results. In group # 1, leukocyte infiltration of the medulla of the kidney with the presence of edema of the stroma was observed. In group # 2, hyperinfiltration of all parts of the kidney was observed, together with the presence of extravasates and severe edema of the stroma. Discussion. Changes revealed by histological examination may indicate that biofilm formation leads to an ineffective immuneresponse, which in turn leads to increased secondary alteration. Conclusions. Biofilm formation is an important factor in the pathogenicity of microorganisms, which affects the course of acute pyelonephritis.